Modernization of Indonesian Islamic Education: Critical Analysis of Madrasa Curriculum Development - Erwin Pinayungan Dasopang; Syahril Rambe (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this writing is to find out the modernization of Indonesian Islamic education: a critical analysis of the development of the madrasa curriculum. The method used is qualitative research with a literature review approach by utilizing literature studies in the form of supporting principles in analyzing this research topic. The findings are 1) Madrasas are educational institutions with Islamic characteristics. Madrasas actually existed during the Mulk Dynasty (still Abbasid) namely the Nizhamiyyah Madrasas. Madrasas grew and developed in Indonesia during the Dutch colonial period, as a form of movement against colonialism and renewal of Islamic education spearheaded by Muslim students. Madrasas as educational institutions began to be recognized by the state since the establishment of the Department of the Minister of Religion in 1946 and regulations for the existence of madrasas continued to receive the government's attention until they were included in the National Education System Law No. 20 of 2003. 2) The reasons for changing the madrasa curriculum were factored in by various influences, ranging from political policies, government regulations, community needs, interests and talents of students and human resource capabilities. 3) The development of the era of development also influences the change of curriculum so that madrasas are able to adapt to the era of modernization and technology